Tailoring Li6PS5Br ionic conductivity and understanding of its role in cathode mixtures for high performance all-solid-state Li–S batteries. Issue 17 (8th April 2019) - Yu, Chuang; Hageman, Jart; Ganapathy, Swapna; van Eijck, Lambert; Zhang, Long; Adair, Keegan R.; Sun, Xueliang; Wagemaker, Marnix
Abstract : By tailoring the Br ordering over the 4a and 4c sites, Li6 PS5 Br with ultrafast ionic conductivity was achieved, which can be worked as both active material and solid electrolyte in all-solid-state Li–S batteries. Abstract : The ultrafast ionic conductivity of Li6 PS5 Br, which is higher than 1 mS cm −1 at room temperature, makes it an attractive candidate electrolyte for the all-solid-state Li–S battery. A simple synthesis route with an easy scale up process is critical for practical applications. In this work, the highest room temperature ionic conductivity (2.58 × 10 −3 S cm −1 ) of Li6 PS5 Br is obtained by an optimal annealing temperature in a simple solid-state reaction method. Neutron diffraction and XRD show that the origin of the highest ionic conductivity is due to the higher purity, smaller mean lithium ion jumps and the optimal Br ordering over 4a and 4c sites. All-solid-state Li–S batteries using a S–C composite cathode in combination with the optimized Li6 PS5 Br electrolyte and Li–In anode show high (dis)charge capacities. Different cycling modes (charge–discharge and discharge–charge) reveal that the capacity of the S–C–Li6 PS5 Br/Li6 PS5 Br/Li–In battery arises from both the active S–C composite and the Li6 PS5 Br in the cathode mixture. The contribution of the latter is verified from all-solid-state batteries using Li6 PS5 Br and its analogues as active materials. Ex situ XRD and electrochemical performance results show that the contribution of capacity from Li6 PS5 Br in the cathode mixture may be associated with the decomposition product Li2 S, while the Li6 PS5 Br in the bulk solid electrolyte layer is stable during cycling.